Kedi : a docalogue - Baron, Jaimie; Fuhs, Kristen (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This second book in the Routledge Docalogue series focuses on a different critical question related to the film from five different scholarly perspectives. The first essay, by Benjamin Schultz-Figueroa looks at Kedi through the lens of environmental collapse. Yiman Wang builds on Schultz-Figueroa's interest in animal studies to compare Kedi to another documentary about stray animals in Istanbul. The third essay, by Paul Reinsch, performs a close analysis of the sound and the music in this documentary, arguing that the diverse score unites the film's mode of address just as much as the distinctive camera-work does. Chris Cagle looks at the film as an example of something that is not quite popular documentary, but not quite art cinema, arguing that this in-between quality suggests something about commerce, identity, and documentary aesthetics in the contemporary mediascape, while Melis Behlil positions the film within Turkish documentary history, problematizing the notion of a national documentary, taking a political economic approach. Finally, the collection concludes with an interview with filmmaker Ceyda Torun. Together these essays touch upon key topics in documentary studies, including animal studies, eco-documentaries, sound studies, festival/industry studies, and digital technology, making them essential reading for scholars interested in contemporary documentary. They also provide useful case studies for teaching documentary film in courses on Contemporary Cinema, Cultural Studies and Media Industries"--
"Routledge Focus" -- taken from front cover.
OCLC-licensed vendor bibliographic record.
Keywords: Kedi (Motion picture); SOCIAL SCIENCE / Media Studies